The Changing Epidemiology of Preterm Twins and Triplets Admitted to Neonatal Intensive Care Units in Canada, 2003 to 2008 - Bassil, Kate L.; Shah, Prakesh S.; Barrington, Keith J.; Harrison, Adele; da Silva, Orlando P.; Lee, Shoo K.; null (American Journal of Perinatology, 2012)
We describe trends in the rates of admission of preterm twin and triplet infants to neonatal intensive care units (NICUs) across Canada and compare their neonatal outcomes over a 6-year period. Temporal trends of admission rates for 5193 twins and triplets < 33 weeks' gestational age to participating NICUs in the Canadian Neonatal Network between 2003 and 2008 were assessed. Trends in infant outcomes were evaluated using logistic regression. The proportion of twins increased from 26.1 to 28.0 per 100 admissions between 2003 and 2008 (7% increase, p = 0.02). In contrast, the proportion of triplets decreased from 5.0 to 3.3 per 100 admissions (34% reduction, p = 0.04). These trends were significant in mothers ≥ 35 years of age. Neonatal outcomes improved for preterm twins (mortality, p <  0.01; survival without any major morbidity, p <  0.01; severe neurological injury, p = 0.02; and severe retinopathy of prematurity, p = 0.03). Similar improvements were observed for triplets, but the sample size was insufficient to reach statistical significance. The rate of NICU admissions for preterm twins at < 33 weeks' gestation has increased in recent years, whereas for triplets it has gradually declined. Neonatal outcomes of preterm twins improved over the study period.
Keywords: multiples; infant; outcomes; preterm